ANALYSIS OF THE CSMA/CA SCHEME FOR WIRELESS LOCAL AREA NETWORKS - OBELOVSKA, Kvitoslava; PELEKH, Khrystyna; PELEKH, Yury; SNAICHUK, Yaromir (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The current stage of telecommunication technologies development is characterized by the rapid growth use of wireless technologies in access networks and the growth requirements for its quality. The bottleneck that significantly reduces the bandwidth of each subscriber connection is that the total bandwidth of the wireless local network is shared among its active members by the shared technology used. The access management sub-layer to the shared physical environment is responsible for this in the network architecture. The main method used at this sub-layer is the Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) scheme. This work is devoted to the analysis of CSMA/CA scheme and the development of an analytical model for its further study and use for the improvement of wireless local networks. The input data is a transition state diagram of a local area wireless network station in data transmission mode. According to the CSMA/CA scheme, stations cannot change their state after starting frame transmission until a confirmation frame of successful reception arrives from the addressee or until the time to wait for it expires. Considering this, it is proposed to use a simplified transition state diagram for the analysis. The operation of the station by the simplified transition state diagram is described using a system of differential equations. As a result of the solution of this system, expressions representing the probability of the station being in each of its states as a function of the intensities of the station’s transitions from each state to another are derived. The values of these intensities depend on both the outgoing traffic of the station and the traffic in the network. The resulting expressions can be used in further work on the analysis of the CSMA/CA scheme, as they make it possible to estimate the operation of the station at different ratios of the station’s output traffic and external traffic generated by other stations of the network. This can be used to develop an enhanced algorithm station operation of wireless local area networks by adapting the parameters of the CSMA/CA scheme to specific current loads of both the station and the network.